Breakthrough therapies: Cystic fibrosis (CF) potentiators and correctors. (19th June 2015) - Solomon, George M.; Marshall, Susan G.; Ramsey, Bonnie W.; Rowe, Steven M.
Summary: Cystic Fibrosis is caused by mutations in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene resulting in abnormal protein function. Recent advances of targeted molecular therapies and high throughput screening have resulted in multiple drug therapies that target many important mutations in the CFTR protein. In this review, we provide the latest results and current progress of CFTR modulators for the treatment of cystic fibrosis, focusing on potentiators of CFTR channel gating and Phe508del processing correctors for the Phe508del CFTR mutation. Special emphasis is placed on the molecular basis underlying these new therapies and emerging results from the latest clinical trials. The future directions for augmenting the rescue of Phe508del with CFTR modulators are also emphasized.Pediatr Pulmonol. 2015; 50:S3–S13. © 2015 Wiley Periodicals, Inc.